Management Information Systems for the Information Age - Haag, Stephen; Cummings, Maeve (Boston McGraw-Hill/Irwin, 2008)
Covers what instructors want students to know about MIS while Extended Learning Modules show students what they can do with MIS.
Include Illustrations, Glossary, Notes and Index.
Keywords: Management information systems -- Information technology -- Information technology--Management